Outdoor thermal comfort research in transient conditions: A narrative literature review - DZYUBAN, Yuliya (Institutional Knowledge at Singapore Management University, 2022)
In recent years, urban planners and designers are paying greater attention to Outdoor Thermal Comfort (OTC) studies due to the imminent threat of the Urban Heat Island and climate change on human health. Historically, indoor thermal comfort research assumed steady-state conditions, centralizing on the concept of thermal neutrality to determine optimal environmental parameters. Such research pivoted to investigating how non-steady-state, transient environmental conditions influence comfort. Recent studies underscore the usefulness of positive alliesthesia in providing a productive framework for OTC evaluation. In this article we first clarify the concepts related to thermal comfort-related terms, scales, and models in the literature. Then, we propose four research questions that we believe are important for the research of thermal transient sensations. To answer them, we present the state of current research and gaps for the field and provide directions that could advance the knowledge on dynamic OTC.